Social inequalities in treatment receipt for childhood cancers in Ireland: A population‐based analysis. Issue 6 (13th November 2021) - Molcho, Michal; Thomas, Audrey A.; Walsh, Paul M.; Skinner, Roderick; Sharp, Linda
Abstract: Treatment advances over the past five decades have resulted in significant improvements in survival from childhood cancer. Although survival rates are relatively high, social disparities in outcomes have been sometimes observed. In a population‐based study, we investigated social inequalities by sex and deprivation in treatment receipt in childhood cancer in Ireland. Cancers incident in people aged 0 to 19 during 1994 to 2012 and treatments received were abstracted from the National Cancer Registry Ireland. Multivariable modified Poisson regression with robust error variance (adjusting for age, and year) was used to assess associations between sex and deprivation category of area of residence at diagnosis and receipt of cancer‐directed surgery, chemotherapy or radiotherapy. Three thousand seven hundred and four childhood cancers were included. Girls were significantly less likely than boys to receive radiotherapy for leukemia overall (relative risk [RR] = 0.70; 95% confidence interval [CI] = 0.50‐0.98), and acute lymphoblastic leukemia specifically (RR = 0.54; 95% CI = 0.36‐0.79), and surgery for central nervous system (CNS) overall (RR = 0.83; 95% CI = 0.74‐0.93) and other CNS (RR = 0.76; 95% CI = 0.60‐0.96). Girls were slightly less likely to receive chemotherapy for non‐Hodgkin lymphoma and surgery for Hodgkin lymphoma (HL), but these results were not statistically significant. Children residing in more deprived areas were significantly less likely to receive chemotherapy for acute myeloid leukemia or surgery for lymphoma overall and HL, but more likely to receive chemotherapy for medulloblastoma. These results may suggest social inequalities in treatment receipt for childhood cancers. Further research is warranted to explore whether similar patterns are evident in other childhood cancer populations and to better understand the reasons for the findings. Abstract : What's new? While treatment and survival outcomes for childhood cancer have improved dramatically over the last five decades, disparities have been observed, particularly relating to demographic and socioeconomic factors. This paper describes findings from an investigation of social inequalities in the treatment of childhood cancer in Ireland. Analyses of National Cancer Registry Ireland data from 1994 to 2012 suggest that, at least for certain pediatric cancers, girls and children who live in the country's most deprived areas have a reduced likelihood of receiving treatment. Additional investigations are needed to determine whether such inequalities exist in other childhood cancer populations and healthcare settings.